Learning together: The dynamics of training teachers for disability inclusion in South Africa - Nseibo, Kofi; Vergunst, Richard; McKenzie, Judith; Kelly, Jane; Karisa, Amani; Watermeyer, Brian (Frontiers in Education, 2022)
Despite the need for inclusive education in South Africa, many teachers have not been appropriately trained for the inclusion process for learners with disabilities in classrooms. A consideration of teacher education for inclusive education involves examining both the structural and professional barriers to training that prevent effective implementation. We review the outcomes of a teacher education project in South Africa through three studies that emanate from Teacher Empowerment for Disability Inclusion (TEDI) at the University of Cape Town. These studies are a situation analysis; a survey of teacher education availability for working with learners with severe disabilities; and an evaluation of short courses. We draw on these studies to develop a holistic picture of the kind of training needed to develop the knowledge, attitudes and skills of teachers to address barriers to learning that arise from disability. This entails a conceptual analysis of how the different elements of training work together to address learner needs.